2018
DOI: 10.1007/s10803-017-3453-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Affect and Restricted and Repetitive Behaviors Measured on the ADOS-2 and Maternal Stress

Abstract: This study investigated categories of autism spectrum disorder (ASD) symptoms measured by the Autism Diagnostic Observation Schedule-Second Edition and their association with maternal stress. Social affect and restricted and repetitive behaviors were compared with levels of maternal stress, measured by the Parenting Stress Index, in 102 children with ASD ages 2-12 years of age. Results indicated that social affect and restricted and repetitive behaviors were associated with the mother's stress regarding accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
6
1
1
Order By: Relevance
“…Even so, parents seem to need some time to implement the strategies they have learned. As a long-term effect, a lower stress level of parents might contribute to an enhancement of the child's development (Keen et al, 2010;Schutte et al, 2018;Crowell et al, 2019). Surprisingly, parents describe a trend to decreased social support in the FETASS group just after training, which is contrary to our hypothesis.…”
Section: Parental Stresscontrasting
confidence: 99%
See 1 more Smart Citation
“…Even so, parents seem to need some time to implement the strategies they have learned. As a long-term effect, a lower stress level of parents might contribute to an enhancement of the child's development (Keen et al, 2010;Schutte et al, 2018;Crowell et al, 2019). Surprisingly, parents describe a trend to decreased social support in the FETASS group just after training, which is contrary to our hypothesis.…”
Section: Parental Stresscontrasting
confidence: 99%
“…As mentioned above, it is well-documented that parents of children with ASD show a higher level of stress (Davis and Carter, 2008;Estes et al, 2009;Hayes and Watson, 2013) and there is some evidence of a relationship between parent stress level and social affect and repetitive or restrictive behavior of the children (Harrop et al, 2016;Schutte et al, 2018). There is growing literature that dysfunctional parent-child interaction and parental stress can have a negative impact on the development of the autistic child (Crowell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, research on PS in families of children with ASD has increased (Abbeduto et al, 2004; Estes et al, 2009) and autism symptoms, cognitive impairment, and emotional and behavioral problems, as well as socio‐demographic features (Schutte et al, 2018) have been identified as variables possibly contributing to the stress of families (Miranda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of studies exploring the relation between severity of autism symptoms and PS (Bader & Barry, 2014; Brei et al, 2015; Hastings et al, 2005; Hastings & Johnson, 2001; Huang et al, 2014; McStay et al, 2014) have produced mixed findings. Studies conducted with gold standard diagnostic instruments for ASD severity, the Autism Diagnostic Observation Schedule ‐ Generic (ADOS‐G; Lord et al, 2000) and the latest edition Autism Diagnostic Observation Schedule‐Second Edition (ADOS‐2; Lord et al, 2012), all failed to report any association between autism symptom severity and PS (Brei et al, 2015; Davis & Carter, 2008; Schutte et al, 2018). Conversely, studies conducted using parent report assessment of lifetime autism symptom severity, such as the Social Communicational Questionnaire—Lifetime (SCQ‐L) (Rutter, Bailey, & Lord, 2003), showed some associations.…”
Section: Introductionmentioning
confidence: 99%
“…The one study examining the relationship between ASD severity and parenting sense of competency suggested that there is lower sense of satisfaction with the parenting role with increased symptom severity of ASD[15]. Some research has attributed the high level of psychological distress among parents of children with autism to the core traits of social communication deficits[10,24] and restrictive, repetitive behaviours[24-26] in their children. These hallmark deficits often make it difficult for parents to form secure, reciprocal relationships with their children[27,28].…”
Section: Introductionmentioning
confidence: 99%